PENGARUH UPAH MINIMUM PROVINSI, PENDIDIKAN DAN KESEHATAN TERHADAP KEMISKINAN DI INDONESIA - Nadia Islami; Ali Anis (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This research aims to examined the impactt of provincial minimum wage, education and health on poverty in Indonesia with the selected model is the Fixed Effect Model (FEM). The data used is panel data during the period 2012-2017, with the technique of collecting documentation data and library studies obtained from relevant institutions and agencies.The variables use are poverty, provincial minimum wage, education and health. The research method used is Ordinary Least Square (OLS). The estimation results show that, provincial minimum wage have a positive and significant effect on poverty in Indonesia. Education have a negative and significant effect on poverty in Indonesia. Health have a negative and its not significant effect on poverty in Indoneisa. Meanwhile simultaneously province minimum wage, education and health affect the poverty in Indonesia.